Aspek Tata Bahasa dalam Buku Teks Bahasa Indonesia Tingkat SMP Kelas VIII - Qurrota Akyun; Yuni Pratiwi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study examines grammar material in Indonesian language textbooks for grade VIII junior high school, specifically within the Merdeka Curriculum framework. The research aims to describe and analyze grammar content in the textbooks, focusing on word structures and the alignment of grammar competencies with learning objectives in each chapter. The research employs a qualitative descriptive method with a document study approach. Data were collected from official textbooks published by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in 2021. Data collection was conducted through document analysis, with the researcher serving as the primary instrument, assisted by an analytical table. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that the grammar material in the textbooks includes word structures such as affixation and reduplication, as well as sentence structures categorized by the presence or absence of clauses, the sequence of subjects and predicates, and the roles of functional elements. The analysis identified two chapters in the grade VIII textbook that contain grammar material and four chapters that do not explicitly include grammar material but align with the stated learning objectives. The study concludes that grammar material in textbooks is essential for enhancing students’ language skills, in line with the principles of the Merdeka Curriculum, which emphasize independence and creativity in learning.